Effects of Salt-Drought Stress on Growth and Physiobiochemical Characteristics of Tamarix chinensis Seedlings - Junhua Liu; Jiangbao Xia; Yanming Fang; Tian Li; Jingtao Liu (The Scientific World Journal)
The present study was designed to clarify the effects of salinity and water intercross stresses on the growth and physiobiochemical characteristics of Tamarix chinensis seedlings by pots culture under the artificial simulated conditions. The growth, activities of SOD, POD, and contents of MDA and osmotic adjusting substances of three years old seedlings of T. chinensis were studied under different salt-drought intercross stress. Results showed that the influence of salt stress on growth was greater than drought stress, the oxidation resistance of SOD and POD weakened gradually with salt and drought stresses intensified, and the content of MDA was higher under severe drought and mild and moderate salt stresses. The proline contents increased with the stress intensified but only significantly higher than control under the intercross stresses of severe salt-severe drought. It implied that T. chinensis could improve its stress resistance by adjusted self-growth and physiobiochemical characteristics, and the intercross compatibility of T. chinensis to salt and drought stresses can enhance the salt resistance under appropriate drought stress, but the dominant factors influencing the physiological biochemical characteristics of T. chinensis were various with the changing of salt-drought intercross stresses gradients.